(untitled) (Research, Society and Development, 2022)
With the objective of demonstrating the factors that act directly and indirectly on the etiology of Bipolar Disorder (BD), using the PICO strategy, were used 24 articles with different views about the origin of BD. Those reveal genetic, biological, and ambiental events that would be able to have influence over the individual independently, but mainly, in conclusion, by interconnecting with one another, having in mind that this disorder has an important heritability, until 80%, which isn’t a single factor in itself but the confluence of multiple factors. Late diagnosis is a proven risk factor with numerous consequences, mainly taking longer to receive the right treatment. Nevertheless, many of the studies about genetics still use animal models, and it may cast doubt on the validity of some arguments, making evident the importance of continuous and new broader scientific projects about BD. Regardless, observations collected in human datasets remain reliable, being possible to reveal risk factors, which may activate epigenetic mechanisms related to Bipolar Disorder development.